PERANCANGAN SISTEM PENCATATAN KEUANGAN DAN PERHITUNGAN PAJAK UMKM BERBASIS EXCEL UNTUK PENENTUAN HARGA POKOK PENJUALAN PADA KUE TRADISIONAL DINA VEZA - Roslita Pandiangan; Eri Bestary Al Haitamy; Ivan Ramadhan (LP2M Politeknik Jambi, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in thenational economy; however, many MSME actors have not yet implementedsystematic and standardized financial recording practices. This condition is alsoexperienced by Dina Veza Traditional Cake MSME, which still relies on manualfinancial records, making it difficult to determine business profits, calculate theCost of Goods Sold (COGS), and fulfill tax obligations accurately. This study aimsto design a Microsoft Excel–based financial recording and tax calculation systemto support accurate COGS determination and assist in calculating the 0.5% FinalIncome Tax for MSMEs in accordance with Government Regulation Number 23 of2018. The research uses a descriptive qualitative approach, with data collectedthrough observation, interviews, and documentation. The financial recordingsystem is developed based on the Financial Accounting Standards for Micro, Small,and Medium Entities (SAK EMKM) and utilizes Microsoft Excel as a practicalrecording tool. The results indicate that the system improves the accuracy andorganization of financial records, facilitates precise COGS calculation, and assistsMSMEs in calculating and reporting Final Income Tax based on business turnovermore effectively